2014
DOI: 10.1182/blood-2014-03-561985
|View full text |Cite
|
Sign up to set email alerts
|

The future of autologous stem cell transplantation in myeloma

Abstract: Autologous stem cell transplantation (ASCT) has long been considered frontline therapy for newly diagnosed myeloma patients. This Spotlight examines the role of ASCT in the era of novel drugs and argues that ASCT should continue to be considered for eligible patients. A combination of novel drugs with ASCT in a sequential treatment approach can attain long-term survival and perhaps cure a subset of patients. ASCT will likely remain an important platform to develop curative strategies in the foreseeable future.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Although real‐world methods for measuring high‐quality response are likely to be less rigorous than those used in clinical trials, we found that physician‐evaluated TTP correlated with depth of response. Furthermore, in accordance with published reports (van Rhee et al , 2014), patients who had undergone SCT were more likely to achieve CR than those who had not. Moreover, efficacy outcomes were broadly similar to those seen in clinical trials (Singhal et al , 1999; Richardson et al , 2005; Dimopoulos et al , 2007; Weber et al , 2007; San Miguel et al , 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Although real‐world methods for measuring high‐quality response are likely to be less rigorous than those used in clinical trials, we found that physician‐evaluated TTP correlated with depth of response. Furthermore, in accordance with published reports (van Rhee et al , 2014), patients who had undergone SCT were more likely to achieve CR than those who had not. Moreover, efficacy outcomes were broadly similar to those seen in clinical trials (Singhal et al , 1999; Richardson et al , 2005; Dimopoulos et al , 2007; Weber et al , 2007; San Miguel et al , 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Although novel agents substantially improved the outcome of first-line therapy, the use of ASCT has not declined over the past years. Importantly, despite data showing that overall survival does not differ comparing upfront and delayed ASCT (13), the following arguments still favour ASCT for eligible patients: The long treatment-free interval, the high quality of life following ASCT, and the possibility for long-term disease-free survival beyond 14 years (14). In consequence, only 8% of patients in the current survey received a delayed ASCT procedure (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest not only that MRD kinetics is more informative than single time-point assessments, but also that this information may be useful to address specific clinical questions (eg, early vs delayed HDT/ASCT for CR patients after induction). 96 Maintenance therapy represents another illustrating example. In the Gruppo Italiano Malattie EMatologiche dell'Adulto (GIMEMA) VEL-03-096 study, Ladetto et al reported PFS rates at median followup of 100% vs 57% for patients in molecular-CR vs MRD-positive cases, respectively.…”
Section: Mrd and Treatment Schemamentioning
confidence: 99%